2012
DOI: 10.1902/jop.2011.110192
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight of Infants of Mothers With Aggressive Periodontitis

Abstract: Background It was hypothesized that if periodontal infections predispose low birth weights and premature birth, then such outcomes should be apparent when the mother has aggressive periodontitis (AgP). Methods Birth weight data were collected by questionnaire from females with AgP, their periodontally healthy siblings, and unrelated periodontally healthy women. Both prospective and retrospective birth outcome data were used. Because many of the periodontal evaluations were performed after the births, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
4
0
4
Order By: Relevance
“…George et al (2011) provided some support for this theory by reporting a significant overall treatment effect in trials that enrolled women with less extensive -although not necessarily less severe -disease. A recent study, however, questions whether adverse pregnancy outcomes are associated with advanced or aggressive forms of periodontitis (Schenkein et al 2012).…”
Section: Interventions Tested To Date Have Been Inadequate To Affect mentioning
confidence: 99%
“…George et al (2011) provided some support for this theory by reporting a significant overall treatment effect in trials that enrolled women with less extensive -although not necessarily less severe -disease. A recent study, however, questions whether adverse pregnancy outcomes are associated with advanced or aggressive forms of periodontitis (Schenkein et al 2012).…”
Section: Interventions Tested To Date Have Been Inadequate To Affect mentioning
confidence: 99%
“…Other studies whose objective was to determine periodontal disease in young population found a prevalence in persons aged between 13 and 20 years of <1%, while in adolescents between the ages of 15 and 17 years, the prevalence was estimated at 0.2% for Caucasians and at 2.6% for Blacks. Similarly, greater prevalence was found in women than in men, and <1% of the population aged under the age of 30 years had AP (20).…”
Section: Epidemiologymentioning
confidence: 94%
“…[20,15,46]. 2012 m. H. A. Schenkein studijoje ištyrus nėš-čiąsias, sirgusias lokalizuotu ir generalizuotu agresyviu periodontitu bei sveikųjų grupę, atsižvelgiant į rūkymą, rasę, amžių, nėštumo trukmę, nerasta statistiškai patikimo ryšio tarp agresyvaus periodontito ir naujagimio svorio [43].…”
Section: Tyrimo Objektas Ir Metodaiunclassified